Expression Levels and Clinical Significance of miR-21-5p, miR-let-7a, and miR-34c-5p in Laryngeal Squamous Cell Carcinoma. (31st August 2017) - Re, Massimo; Magliulo, Giuseppe; Gioacchini, Federico M.; Bajraktari, Arisa; Bertini, Andrea; Çeka, Artan; Rubini, Corrado; Ferrante, Luigi; Procopio, Antonio D.; Olivieri, Fabiola
Abstract : Objective . Altered microRNAs (miRNAs) expression has been found in many cancer types, including laryngeal squamous cell carcinoma (LSCC). The aim of this study was to determine the role and clinical value of three LSCC-related miRs, such as miR-21-5p, miR-let-7a, and miR-34c-5p in a homogeneous cohort of patients with primary LSCC treated by primary surgery. Methods . Expression levels of miR-21-5p, miR-let-7a, and miR-34c-5p were detected in 43 pairs of LSCC and adjacent normal tissues by reverse-transcription quantitative PCR. Overall survival and disease-free survival were evaluated using the Kaplan–Meier method, and multivariate analysis was performed using the Cox proportional hazard analysis. Results . miR-21-5p is significantly upregulated, while miR-let-7a is significantly downregulated in LSCC tumor tissues compared with the corresponding adjacent normal tissues. The downregulation of miR-34c-5p expression significantly correlated with a shorter disease-free survival and, in the multivariate analysis, low miR-34c-5p expression was associated with an increased risk of recurrence. Conclusions . miR-21-5p, miR-let-7a, and miR-34c-5p seem to play a critical role in LSCC carcinogenesis and might have a diagnostic and prognostic clinical value. The miR-let-7a levels could have a predictive role for lymph node metastases and miR-34c-5p might be a promising biomarker of patient outcome.